2020
DOI: 10.17818/emip/2020/2.12
|View full text |Cite
|
Sign up to set email alerts
|

Employee-Related Indicators in the Non-Financial Reporting in Hospitality Industry

Abstract: Due to many social and environmental challenges in the last decade, many companies recognized the importance of non-financial reporting to provide complete overview of its performance and socially responsible behaviour. Furthermore, for some companies the obligation of non-financial reporting has been institutionalized by European commission directives. This paper explores the extent of non-financial reporting regarding employment-matters in hospitality industry in Croatia. Research objective of the paper is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Therefore, the main advantage of using the above methods and calculation formulas is the quality of the calculation and the elimination of incorrectness (Krivokapić et al, 2017; Thompson et al, 2015). Especially, this is relevant when determining indicators such as the potential value of the synergistic effect, the cost of the combined organization taking into account synergy, the cost of the buying organization, the cost of the acquired organization, the risk of not achieving positive synergies, and the premium paid to the organization being sold by the buying organization and transaction costs (Itami & Roehl, 1987; Mohindru & Chander, 2010; Pavić & Pervan, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the main advantage of using the above methods and calculation formulas is the quality of the calculation and the elimination of incorrectness (Krivokapić et al, 2017; Thompson et al, 2015). Especially, this is relevant when determining indicators such as the potential value of the synergistic effect, the cost of the combined organization taking into account synergy, the cost of the buying organization, the cost of the acquired organization, the risk of not achieving positive synergies, and the premium paid to the organization being sold by the buying organization and transaction costs (Itami & Roehl, 1987; Mohindru & Chander, 2010; Pavić & Pervan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Next, the value of both companies is determined, but without considering synergy (Pavić & Pervan, 2010). Then the cost of businesses with a synergistic effect (allowing for changes in CF (cash flow)) is considered.…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…On the other hand, Cummins and Nini (2002), concluded that diversification has inverse effect on firm profitability. Pavić and Pervan (2010) and Lee and Kang (2015) also found that diversification has a significant negative influence on profitability. Lee (2017) also analyzed product diversification's impact on firm performance among insurance firms and found significant negative effect on insurer's performance.…”
Section: Why Diversifymentioning
confidence: 94%
“…Dalekosežnost posljedica važnih nalaza istraživanja u području ovu temu čini istraživački aktivnom i danas (Madžar & Milohnić, 2019;Načinović Braje, Pavić & Ferjanić Hodak, 2020;Bakotić, 2021;Andrijić, 2022;Pandža Bajs & Tomas, 2023).…”
Section: Uvodunclassified